Comparison of Indonesian and South Korean Criminal Systems in Child Crime: Restorative Justice Review - Abdullah, Nadia Rahmatiya (Universitas Negeri Gorontalo, 2025)
This study explores the implementation of restorative justice in Indonesia's juvenile justice system, focusing on the challenges and opportunities for improving the rehabilitation of juvenile offenders. Restorative justice, a model that emphasizes repairing harm through dialogue and mutual agreement between offenders, victims, and the community, offers an alternative to punitive measures traditionally used in criminal justice systems. The research examines the legal framework provided by the Indonesian Juvenile Justice System under Law No. 11 of 2012 and its application in practice. Despite the positive intentions of the law, several obstacles hinder the effective implementation of restorative justice, including inadequate rehabilitation facilities, a lack of understanding and training among law enforcement officers, and a prevailing punitive culture within the judicial system. The study highlights the need for greater access to rehabilitation programs, comprehensive training for legal practitioners, and increased public awareness of the benefits of restorative justice. Additionally, it emphasizes the importance of including victim participation and family involvement in the restorative process to enhance its effectiveness. The findings suggest that, with the appropriate reforms, restorative justice can provide a more rehabilitative approach to juvenile crime in Indonesia, offering a pathway for young offenders to reintegrate into society and avoid the negative consequences of imprisonment